2019
DOI: 10.3390/su11082196
|View full text |Cite
|
Sign up to set email alerts
|

Where to Preserve? Evaluating the Integrity Principle for Delineating Protection Scopes of Kaiping Diaolou and Villages

Abstract: While establishing where to preserve in a world heritage site is critical for heritage protection, management and cultural sustainability, the approach to delineating protection scopes under the integrity principle remains less discussed in literature. This study explores a quantitative approach to evaluating the preservation scopes of the Kaiping Diaolou and Villages (KDVs), a world culture heritage in south China. Diaolous are multiple-story tower dwellings, originally built for defense purposes in the villa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The clustering validity analysis is conducted by utilizing a weighted Minkowski distance definition that takes into account the contribution of each attribute feature parameter [15]. The validity of clustering based on external or internal criteria relies on statistical assumptions, and under different assumptions and setting different parameters for the division of entropy coefficients for fuzzy clustering, the objects of data within a class are usually closer to each other than the distance between the objects of data belonging to different classes, defined as:…”
Section: Accumulation Of Cultural Similaritiesmentioning
confidence: 99%
“…The clustering validity analysis is conducted by utilizing a weighted Minkowski distance definition that takes into account the contribution of each attribute feature parameter [15]. The validity of clustering based on external or internal criteria relies on statistical assumptions, and under different assumptions and setting different parameters for the division of entropy coefficients for fuzzy clustering, the objects of data within a class are usually closer to each other than the distance between the objects of data belonging to different classes, defined as:…”
Section: Accumulation Of Cultural Similaritiesmentioning
confidence: 99%
“…On the one hand, many studies have surveyed the transition of the dominant morphology in rural China [28,30,31], especially relative to hollowed villages and rural restructuring [32]. These studies focus on the change of rural construction land in terms of its quantity and morphology, as well as the transformation between construction land and other land use.…”
Section: Land Use Transition In Rural Chinamentioning
confidence: 99%
“…Others studied the pattern characteristics of pigments (Sun et al 2019). Yin et al (2019) and Zhang et al (2020) discussed the construction and heritage protection of Kaiping Diaolou pigments and proposed some protection methods and measures. Zeng et al (2011) found that the decorative patterns of pigments in Kaiping Diaolou buildings can be roughly divided into four types: plant patterns, animal patterns, text patterns, and geometric patterns.…”
Section: Introductionmentioning
confidence: 99%